Comparison of the presentation and electrophysiological characteristics of autoimmune nodopathies in patients with antibody-negative CIDP and CMT1 - Song, Changdong; Liu, Hengfang (Frontiers in Neurology, 2025)
PurposeAutoimmune nodopathy (AN), as patients positive for IgG4 autoantibodies against NF155, NF186, CNTN1, or CASPR1, is a distinct form of chronic inflammatory demyelinating polyneuropathy (CIDP) that shares similar clinical and electrophysiological characteristics with Charcot–Marie–Tooth disease type 1 (CMT1). This study aimed to determine the clinical presentation and electrophysiological features of AN and compare them with antibody-negative CIDP and CMT1.MethodsWe collected clinical data from 29 patients who met the European Federation of Neurological Societies/Peripheral Nerve Society (EFNS/PNS) electrophysiological diagnostic criteria for definite CIDP. Autoimmune antibodies (anti-NF155, NF186, CNTN1, and CASPR1) were tested using cell-based assays. Additionally, 17 CMT1 patients, diagnosed with hereditary motor sensory neuropathy type 1, were included. We compared the clinical and electrophysiological characteristics of AN, antibody-negative CIDP, and CMT1 patients.ResultsAmong the 29 CIDP patients, 10 tested positive for autoantibodies (8 for NF155, 1 for CASPR1, and 1 for CNTN1). AN patients had a younger age of onset compared to antibody-negative CIDP and were similar in age to CMT1 patients. Hand tremor was more common in AN patients (60%) compared to antibody-negative CIDP (21%) and CMT1 (5.8%). Conversely, 76.4% of CMT1 patients exhibited cavus foot, significantly higher than the 20% in AN patients. Cerebrospinal fluid (CSF) analysis revealed higher cell count and protein levels in AN patients compared to antibody-negative CIDP and CMT1. AN patients showed poor response to corticosteroids and intravenous immunoglobulin (IVIG), but rituximab was more effective. Electrophysiological findings revealed significantly prolonged distal motor latencies (DML) in the tibial posterior and peroneal nerves, as well as prolonged F-wave latencies in the ulnar and posterior tibial nerves in AN patients than antibody-negative CIDP. In contrast, compared with AN, CMT1 patients showed prolonged DML and significantly reduced motor conduction velocities (MCV) in the median and ulnar nerves. AN patients exhibited sparing of the sural nerve, whereas this phenomenon was not observed in CMT1 patients.ConclusionIn young male patients with hand tremors, demyelinating electrophysiological features (especially prolonged DML and F-wave latencies), elevated CSF protein levels, and poor response to corticosteroids, autoimmune nodopathy, AN antibody testing is recommended. Compared to AN, CMT1 patients tend to have a slower disease course, less frequent tremors, and normal CSF protein levels. A median nerve DML greater than 10 ms and MCV less than 25 m/s supports a diagnosis of CMT1.